(untitled) (Research, Society and Development, 2022)
Objective: Identify evidence of social inclusion and exclusion perceived by family members, due to living with a person diagnosed with Autism Spectrum Disorder (ASD). Methodology: The study was conducted following a qualitative approach, in which five families that live with a person diagnosed with ASD were part of our analysis, involving fathers (2), mothers (5), brothers (2) and grandmother (1). Data collection was carried out through recorded interviews, using the Critical Incident Technique, and data were organized using Bardin’s thematic content analysis. Results: Two thematic categories emerged: “The context of autistic life and its adversities facing stigma and exclusion" and "A positive view of Autism Spectrum Disorder." The first addresses the adversities and difficulties faced in identifying the disorder and in the process of family adaptability. This category also takes into consideration society’s and family’s lack of knowledge about ASD, which leads to social exclusion. The second category exhibits lessons learned while living with a person diagnosed with ASD. Conclusion: Furthermore, it portrays the adaptation and growth occurred in intrafamily relationships. Therefore, daily living with a person with ASD is characterized by adversity, stigma and social exclusion. However, it also distinguishes the resilience and overcoming of family members.